Immobilization tools and materials selection in dentoalveolar fracture - Samsudin, Endang (Universitas Padjadjaran, 2007)
Dentoalveolar fracture treatment can be performed in a simple way without surgery by reposition the fractured fragment and establish immobilization. One of the factors affecting the success of dentoalveolar fracture treatment is immobilization material and technique selection. The purpose of this study is to provide illustration about various materials used to perform immobilization in the dentoalveolar area and the objective is to obtain optimal immobilization.